PENGARUH REGULASI DIRI TERHADAP MOTIVASI AKADEMIK SISWA SMP X DI JAKARTA - Basaria, Debora; Zamralita, Zamralita; Margaretha, Jane (Provitae: Jurnal Psikologi Pendidikan, 2024)
The COVID-19 pandemic has impacted education, limited students' social environment and decreasing their motivation to learn. In Indonesia, 7 out of 10 students revealed that they rarely study since the introduction of social restrictions. Motivation is an important aspect in the learning process, students with high motivation will strive for the best results. Learning motivation comes from internal and external drives that change behavior. Students need good self-regulation skills to manage internal and external motivational drives. Self-regulation contributes positively to academic achievement and predicts long-term educational success. This study aims to determine the effect of self-regulation on academic motivation of SMP X students. The participants in this study consisted of 141 students aged 11-15 years. The researcher used the Academic Motivation Scale (AMS) and Personal Self-Concept (PSC) Questionnaire which have been translated into Indonesian. Results showed a significant positive effect between self-regulation and academic motivation, with R2 = 0.135, F value = 7.12, and p value of 0.00 < 0.5. This indicates higher student self-regulation correlates with higher academic motivation. Effective self-regulation strategies can help increase student motivation amid pandemic-like disruptions.